2022
DOI: 10.4103/ajts.ajts_90_21
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with vasovagal reactions in whole blood donors

Abstract: BACKGROUND: Vasovagal reactions to blood donation though generally mild and account for about 1% of donations, causes embarrassment/injury to the donors, lower likely return rates for future donations etc. The workforce hours devoted to attending to those who reacted can also affect the efficiency of the blood centre. There are various factors, both modifiable and nonmodifiable, involved in the causation of such reactions. OBJECTIVES: This study sought to identify the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…And Shivhare et al also found that a significant correlation existed between having disturbed sleep the night before blood donation and vasovagal reaction (OR: 4.4; 95% CI 2.8-6.9) [17]. These studies were similar to the findings in our study.…”
Section: Subgroup Analysessupporting
confidence: 91%
See 4 more Smart Citations
“…And Shivhare et al also found that a significant correlation existed between having disturbed sleep the night before blood donation and vasovagal reaction (OR: 4.4; 95% CI 2.8-6.9) [17]. These studies were similar to the findings in our study.…”
Section: Subgroup Analysessupporting
confidence: 91%
“…The vasovagal reactions were the most common type of ADR, accounting for 67%–95% of all ADR [29]. Vasovagal reactions result from a neurophysiological reflex during or after venipuncture, including nausea, dizziness, sweating, pallor changes or even fainting [17]. The autonomic nervous system plays an important role in the coordination of several physiological functions including the sleep process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations